2022
DOI: 10.3390/met12081309
|View full text |Cite
|
Sign up to set email alerts
|

A New Computational Method for Predicting Ductile Failure of 304L Stainless Steel

Abstract: Austenitic stainless steel is useful for storing and transporting liquefied natural gas (LNG) at temperatures below −163 °C due to its superior low-temperature applications. This study develops a computational method for the failure prediction of 304L stainless steel sheet to utilize its usability as a design code for industrial purposes. To consider material degradation in a phenomenological way during the numerical calculation, the combined Swift–Voce equation was adopted to describe the nonlinear constituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 54 publications
0
9
0
1
Order By: Relevance
“…Over the past two decades, it has been shown that stress triaxiality alone cannot explain the reduction in ductility observed for some classes of materials when subjected to shear-dominated stress states. Such behavior has been reported for aluminum alloys [4,5], Ti-6Al-4V [6], Weldox [7], and 304L steel [8]. This evidence motivated several studies in considering the third deviatoric stress invariant effect in plasticity [9][10][11][12] and damage model [13][14][15][16][17] formulations.…”
Section: Introductionmentioning
confidence: 57%
“…Over the past two decades, it has been shown that stress triaxiality alone cannot explain the reduction in ductility observed for some classes of materials when subjected to shear-dominated stress states. Such behavior has been reported for aluminum alloys [4,5], Ti-6Al-4V [6], Weldox [7], and 304L steel [8]. This evidence motivated several studies in considering the third deviatoric stress invariant effect in plasticity [9][10][11][12] and damage model [13][14][15][16][17] formulations.…”
Section: Introductionmentioning
confidence: 57%
“…However, coupling can complicate the model in some cases, making its numerical implementation challenging. Kim et al (2022) employed Swift-Voce hardening equation coupled with MMC fracture criterion to characterize the non-linear response beyond the ultimate tensile strength of 304L stainless steel.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the constitutive relations of materials established by macroscopic phenomenological method have been studied extensively in the world. Macroscopic phenomenological models include the Rice and Tracy fracture model [17], Bai-Wierzbicki model [18], DF series fracture criterion [19], JC (Johnson-Cook) fracture model [20], MC (Mohr-Coulomb fracture) model [21], MMC (Modified Mohr-Coulomb Model) fracture model [22], and DIEM (Damage Initiation and Evolution Model) fracture model [23]. JC, MMC, and DIEM are the most commonly used models of metal materials used in automotive engineering.…”
Section: Introductionmentioning
confidence: 99%